An overview on visible light responsive metal oxide based photocatalysts for hydrogen energy production. Issue 76 (19th August 2015) - Martha, Satyabadi; Chandra Sahoo, Prakash; Parida, K. M.
<x xml:space="preserve">Abstract</x> The present review summarizes the recent development and challenges in visible light responsive metal oxide based photocatalysts for water splitting.